2020
DOI: 10.3390/ma13163650
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Enriched Cr1−xAlxN Multilayer-Like Coatings Manufactured by Dynamic Glancing Angle Direct Current Magnetron Sputtering

Abstract: Multilayer-like CrN and Cr1−xAlxN coatings with different Al contents were deposited onto a stainless steel substrate using dynamic glancing angle deposition direct current magnetron sputtering (DGLAD dcMS) in a N rich atmosphere to understand the role of Al on the growth of the films and mechanical properties of the nitrides with a multilayer architecture. Chemical analysis by means of energy dispersive analysis (EDS) and glow discharge optical emission spectroscopy (GDOES) depth profiling revealed that while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…The sample holder is part of a carousel that can perform oscillatory movements rocking the sample in front of the target surface in a predetermined angular range and period. This particular setup has been described in detail in previous publications and is responsible for creating the DGLAD motion [ 25 , 28 , 29 ]. By rocking the substrate, the angle of incidence of the flux from the target (zenith) is continuously varied between the angular limits established and at a speed corresponding to the period of duration of the oscillations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample holder is part of a carousel that can perform oscillatory movements rocking the sample in front of the target surface in a predetermined angular range and period. This particular setup has been described in detail in previous publications and is responsible for creating the DGLAD motion [ 25 , 28 , 29 ]. By rocking the substrate, the angle of incidence of the flux from the target (zenith) is continuously varied between the angular limits established and at a speed corresponding to the period of duration of the oscillations.…”
Section: Methodsmentioning
confidence: 99%
“…This technique also produces coatings with nanosculpted grains, in the form of a zig-zag, for instance. The authors found correlations between these structures and variations on hardness and texture of the coatings [ 27 ], as well as misorientation gradients and the zigzag grains corresponding to the oscillatory motion of the substrate [ 25 , 28 , 29 ]. This showed a potentiality in tailoring the mechanical performance of hard coatings by engineering the sculpture of their grains.…”
Section: Introductionmentioning
confidence: 99%
“…ASTM G133-05 standard was followed to calculate wear volume and wear rate 6 cross section profiles from the trench of each sample were extracted and their area were calculated to obtain a mean area of loss material, that was multiplied by the total sliding distance to determine the average wear volume. The ( 200) is the preferential orientation for all coatings, which is expected for Cr-Al-N in conditions of high adatom mobility AVILA et al, 2020).…”
Section: Characterizationmentioning
confidence: 69%
“…Therefore, the rocking oscillatory motion of the substrate during The results of EDS measurements for the conditions of no oscillation, ± 10° and ± 20° for dcMS and HiPIMS samples are listed in Table 4. It is evident that the coatings presented high N content as a result of target poisoning and low sputtering yield of Al containing targets in reactive atmosphere (AVILA et al, 2020). No systematic dependence of the chemical composition with the oscillatory range can be observed.…”
Section: Characterizationmentioning
confidence: 92%
See 1 more Smart Citation